The Implementation of Article 29 UUD 1945 as an Embodiment of Religious Tolerance in Indonesia: An Islamic Law Perspective - Oheo K. Haris; Muhammad Yazid (Universitas Islam Negeri Alauddin Makassar, 2016)
This article discusses the implementation of article 29 UUD 1945 as an embodiment of religious tolerance in Islamic law perspective. Religious tolerance has become an essential object, this because of pluralism cultures and various religions which have been naturally developed as well as accepted by all of the citizens. If this could not well-managed in an atmosphere of good cooperation, then it is possible that differences in religious culture would have trigger social conflict. The findings suggest on that article provision on 29 Indonesian Constitution contained; (a) Believing and god-fearing on Oneness God in accordance with human civilized; (b) Construct the respect and tolerance among religions; (c) Admitting that every citizen free to worship and not to impose the will on other people's religion. This respect is merely to look for and find out the similarity and equality that may have advantages as comparative materials.